Kajian Teknis Geometri Jalan Tambang Front 242 Untuk Pencapaian Produktivitas Alat Angkut Di PT Semen Padang (Persero) Tbkntuk Pencapaian Produktivitas Alat Angkut Di PT Semen Padang (Persero) Tbk - Jeffry Reynold Silalahi; Delita Ega Andini; Guskarnali Guskarnali (MINERAL, 2018)
PT Semen Padang (Persero) Tbk is one of the cement producing companies in Indonesia. The supply of limestone used as the main raw material in the manufacture of cement is obtained through the mining process in the IUP area of ​​the company. Mining roads are one of the facilities that must be considered in limestone mining activities because it is a major support in the process of transporting limestones obtained from the working Front. Inadequate road conditions can lead to less productive means of transport in the transport process, which causes production inaccessibility. The mining roads in the 242 working Front are considered to be poor so that a technical study of the mine road is required in accordance with the AASHTO Manual Rular Highway Design standard so that the geometry of the mine road is not good enough so that improvements can be made, engineering studies include road width, cross slope, superelevation, road slope, as well as a study of the carrying capacity of the soil and the influence of the mine road on fuel consumption. Based on the results of the study, the geometry of the mine road is as followsthe haulage width of one lane is minimum 14 m, the width of the haul road is two lanes of 24 m, the width of the two lanes is 25 m minimum, the superelevation value is 1%, cross slope is 48 cm, the slope can be 16% of the vehicles are transported while the slope based on AASHTO is 10%, the slope of the road becomes the biggest factor that influences fuel consumption because it makes the conveyance exert great power. Mine path geometry that is not suitable causes a time of barrier of 86.85 seconds with a cycle time of 22.3 minutes using an average speed of 15 km / h resulting in a production of 1,343.04 tons / hour, while if made temporary road the transport means can reach ideal speed with time on average 29 km / h and 27 km / h, cycle time 17.75 minutes with a production of 1,687.4 tons / hour.